Serine protease from Tricosanthus tricuspidata accelerates healing of Echis carinatus venom-induced necrotic wound. (August 2020) - Rudresha, Gotravalli V.; Manjuprasanna, Vaddarahally N.; Urs, Amog P.; Choudhury, Manisha; Rajaiah, Rajesh; Vishwanath, Bannikuppe S.
Abstract: Echis carinatus (EC) envenomation causes severe immune response by the accumulation of tissue debris in the form of DAMPs resulting in chronic inflammation and progressive tissue necrosis at the bitten site. Clearing of tissue debris is a prerequisite to enhance the healing of venom-induced necrotic wounds. Tricosanthus tricuspidata is a medicinal plant used extensively for the treatment of snake bite-induced toxicities. The active component responsible for the observed pharmacological action is a serine protease, tricuspidin. The topical application of tricuspidin was able to neutralize ECV-induced mouse footpad tissue necrosis and open wound in rabbits. Tricuspidin exerted its healing action via proteolytic activity as a consequence of upregulation of MMP-8 and down regulation of MMP-9. Further, tricuspidin reduced ECV-induced inflammation by decreasing the expression of TNF-α, IL-6 and MPO, and by increasing the level of VEGF-A and TGF-β1. The modulation of ECV induced immune/inflammatory mediators by tricuspidin was found to be more effective than trypsin. Moreover, tricuspidin and trypsin activated MAPKs via protease activated receptors-2 (PAR-2). These data indicate that the proteolytic activity of tricuspidin directly involved in the healing of ECV-induced chronic wound. Highlights: Echis carinatus venom causes progressive tissue necrosis in mice and rabbits. Tricuspidin accelerates healing of Echis carinatus venom-induced necrotic wound. Enhanced wound healing by tricuspidin is attributed to proteolytic activity. Tricuspidin reciprocally regulates MMP-8 and -9 expression and reduced inflammation.